Effect of Chromium Doping to Hardness Properties in the Manufacture of Spur Gears Made from Ferrous Powder - Albert Daniel Saragih; Slamet Sutjipto (Jurnal Teknik Mesin (JTM), 2020)
A gear is a part of a machine that has a very complex shape so that it requires special care and expertise in the manufacturing process. Powder metallurgy offers an efficient manufacturing process for the production of these complex machining parts. In this study, Cr metal powder was selected to increase the hardness properties of spur gears made from iron (Fe) powder. Doping Cr by 0%; 0.5%; 10%, 1.5% and 2.0% will be added in gear manufacturing. Water is used as a binder with a ratio of 1:15 which is then packed by 15,000 kg or 15 tons then heated or sintered at a temperature of 1200 oC for 1 hour. The shrinkage ratio of the sample to the sintering treatment averaged 4.6%. 0.2 kg of load applied to the Vickers hardness test. Vickers hardness values obtained were 60, 77, 90, 184 and 211 respectively for the Cr doping of 0%; 0.5%; 10%, 1.5% and 2.0%. From these data it is found that the addition of the element Cr increases the hardness properties of iron gears. The hardness value shown is still too small, this is because there is still a lot of porosity generated in the sintering process because it is not in a vacuum condition.